Introducing Mathematical Models to Define Settling Curves in Designing Thickeners - Garmsiri, MR; Haji Amin Shirazi, H; Yahyaei, M (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
Thickener design is based on settling tests and settling curves. In a settling curve, the mud line (interface between the settled pulp and clean water) height is plotted versus time. In this paper three mathematical models are introduced to define settling curves. Approximately 300 settling tests with varying feed solids concentration and flocculant types and dosages using iron, copper, coal, lead and zinc were conducted to verify equations. The coefficient of determination (R2) was used to evaluate the validation of equations. It is shown that with the first model in 98% of cases, and with the second and third models in 99 and 100% of the cases, R2 was greater than 0.99. A quick interpretation of the settling test results, simple determination of critical point and error corrections are considered to be benefits of the presented mathematical models.